2020
DOI: 10.1038/s41467-020-18432-6
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal hub neurons maintain distinct connectivity throughout their lifetime

Abstract: The temporal embryonic origins of cortical GABA neurons are critical for their specialization. In the neonatal hippocampus, GABA cells born the earliest (ebGABAs) operate as ‘hubs’ by orchestrating population synchrony. However, their adult fate remains largely unknown. To fill this gap, we have examined CA1 ebGABAs using a combination of electrophysiology, neurochemical analysis, optogenetic connectivity mapping as well as ex vivo and in vivo calcium imaging. We show that CA1 ebGABAs not only operate as hubs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 57 publications
3
46
0
Order By: Relevance
“…The significantly higher E/I ratio received by these cells suggests that they may be preferentially recruited by synaptic excitation, since they are otherwise less intrinsically excitable (lower Rm, low firing rate in response to long depolarizing current injections, lower sag). Interestingly, the same lower excitability (across similar metrics), combined with lower levels of PV inputs was observed in early born CA1 GABAergic neurons and DG granule cells (Bocchio et al, 2020; Gupta et al, 2012; Save et al, 2019), again indicating similar fates in the adult across different subtypes of pioneer neurons.…”
Section: Discussionmentioning
confidence: 60%
“…The significantly higher E/I ratio received by these cells suggests that they may be preferentially recruited by synaptic excitation, since they are otherwise less intrinsically excitable (lower Rm, low firing rate in response to long depolarizing current injections, lower sag). Interestingly, the same lower excitability (across similar metrics), combined with lower levels of PV inputs was observed in early born CA1 GABAergic neurons and DG granule cells (Bocchio et al, 2020; Gupta et al, 2012; Save et al, 2019), again indicating similar fates in the adult across different subtypes of pioneer neurons.…”
Section: Discussionmentioning
confidence: 60%
“…Highly connected but rare hub neurons have been of great interest for studies working towards the goal of advancing seizure control with minimal side-effects 79 . This has been motivated by experimental work showing that hub neurons orchestrate network synchrony 12,13 and by computational work predicting their role in the transition from interictal to ictal discharge 11 .…”
Section: Discussionmentioning
confidence: 99%
“…One conserved feature of complex networks is the presence of richly connected yet sparse hub neurons 10 . It has been shown that these neurons are critical for influencing network dynamics in biological neural circuits 1113 . Specifically, experimental studies have shown that hub neurons orchestrate network synchrony in the developing brain 12 and maintain their effectiveness in adulthood 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal cell populations are activated during simple locomotion 25 and during a motor learning task 12 . Less clear is whether this activation is cooperative, independent or competitive with the rest of the motor systems such as the striatum or motor cortex 3 .…”
Section: Resultsmentioning
confidence: 99%